The Formulation’s Technique Using Microbes to the Speed Decomposition of Biomass Fertilizers. - M Rofi'i; Ambar Susanti; Siti Aminatuz Zuhria (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Potential biomass such as rice straw, Eichornia crassipes and cow dung can be used as raw material for compost. This study aims to determine the ratio of the composition of the best raw materials and determine the minimum time required to produce quality compost. This study used a comparative treatment dose composition of K1 = Cow dung 25% + Straw 50% + Eichornia crassipes 25%, K2 = Cow dung 25% + Straw 25% + Eichornia crassipes 50%, K3 = Cow dung 50% + Straw 25% + Eichornia crassipes 25%.The weight of the material for each treatment is 5kg. This study used 2 local isolates of trichoderma sp, EM4 and without Decomposer for comparison. The composting process lasts for 21 days with temperatures ranging from 28,1°C - 35°C. Compost humidity range 80 to 85%, and pH ranges from 6.5 to 7.5. In general, the quality of the compost produced is in accordance with SNI 19-7030-2004 with K3Mt = 50% cow dung + 25% straw + 25% Eichornia crassipes, with the addition of local microbe Trichoderma sp Isolate can conclude the physical properties of compost. Color (3.83), Smell (4.42), Texture (3.83), and Temperature (29,75 °C), pH 7, humidity 85% with the best test results.